First-in-human study of an OX40 (ivuxolimab) and 4-1BB (utomilumab) agonistic antibody combination in patients with advanced solid tumors. Issue 10 (27th October 2022) - Hamid, Omid; Chiappori, Alberto A; Thompson, John A; Doi, Toshihiko; Hu-Lieskovan, Siwen; Eskens, Ferry A L M; Ros, Willeke; Diab, Adi; Spano, Jean-Philippe; Rizvi, Naiyer A; Wasser, Jeffrey S; Angevin, Eric; et al.
Abstract : Background: Ivuxolimab (PF-04518600) and utomilumab (PF-05082566) are humanized agonistic IgG2 monoclonal antibodies against OX40 and 4-1BB, respectively. This first-in-human, multicenter, open-label, phase I, dose-escalation/dose-expansion study explored safety, tolerability, pharmacokinetics, pharmacodynamics, and antitumor activity of ivuxolimab+utomilumab in patients with advanced solid tumors. Methods: Dose-escalation: patients with advanced bladder, gastric, or cervical cancer, melanoma, head and neck squamous cell carcinoma, or non-small cell lung cancer (NSCLC) who were unresponsive to available therapies, had no standard therapy available or declined standard therapy were enrolled into five dose cohorts: ivuxolimab (0.1–3 mg/kg every 2 weeks (Q2W)) intravenously plus utomilumab (20 or 100 mg every 4 weeks (Q4W)) intravenously. Dose-expansion: patients with melanoma (n=10) and NSCLC (n=20) who progressed on prior anti-programmed death receptor 1/programmed death ligand-1 and/or anti-cytotoxic T-lymphocyte-associated antigen 4 (melanoma) received ivuxolimab 30 mg Q2W intravenously plus utomilumab 20 mg Q4W intravenously. Adverse events (AEs) were graded per National Cancer Institute Common Terminology Criteria for Adverse Events V.4.03 and efficacy was assessed using Response Evaluation Criteria in Solid Tumors (RECIST) V.1.1 and immune-related RECIST (irRECIST). Paired tumor biopsies and whole blood were collected to assess pharmacodynamic effects and immunophenotyping. Whole blood samples were collected longitudinally for immunophenotyping. Results: Dose-escalation: 57 patients were enrolled; 2 (3.5%) patients with melanoma (0.3 mg/kg+20 mg and 0.3 mg/kg+100 mg) achieved partial response (PR), 18 (31.6%) patients achieved stable disease (SD); the disease control rate (DCR) was 35.1% across all dose levels. Dose-expansion: 30 patients were enrolled; 1 patient with NSCLC achieved PR lasting >77 weeks. Seven of 10 patients with melanoma (70%) and 7 of 20 patients with NSCLC (35%) achieved SD: median (range) duration of SD was 18.9 (13.9–49.0) weeks for the melanoma cohort versus 24.1 (14.3–77.9+) weeks for the NSCLC cohort; DCR (NSCLC) was 40%. Grade 3–4 treatment-emergent AEs were reported in 28 (49.1%) patients versus 11 (36.7%) patients in dose-escalation and dose-expansion, respectively. There were no grade 5 AEs deemed attributable to treatment. Ivuxolimab area under the concentration–time curve increased in a dose-dependent manner at 0.3–3 mg/kg doses. Conclusions: Ivuxolimab+utomilumab was found to be well tolerated and demonstrated preliminary antitumor activity in selected groups of patients. Trial registration number: NCT02315066 .